Environmental DNA metabarcoding for freshwater bivalves biodiversity assessment: methods and results for the Western Palearctic (European sub-region) - Vincent Prié; Alice Valentini; Manuel Lopes-Lima; Elsa Froufe; Mathieu Rocle; Nicolas Poulet; Pierre Taberlet; Tony Dejean (Hydrobiologia, 2021)

The future of fish‐based ecological assessment of European rivers: from traditional EU Water Framework Directive compliant methods to eDNA metabarcoding‐based approaches - Didier Pont; Alice Valentini; Mathieu Rocle; Anthony Maire; Olivier Delaigue; Pauline Jean; Tony Dejean (Journal of Fish Biology, 2021)
Most of the present EU Water Framework Directive (WFD) compliant fish‐based assessment methods of European rivers are multi‐metric indices computed from traditional electrofishing (TEF) samples, but this method has known shortcomings, especially in large rivers. The probability of detecting rare species remains limited, which can alter the sensitivity of the indices. In recent years, environmental (e)DNA metabarcoding techniques have progressed sufficiently to allow applications in various ecological domains as well as eDNA‐based ecological assessment methods. A review of the 25 current WFD‐compliant methods for river fish shows that 81% of the metrics used in these methods are expressed in richness or relative abundance and thus compatible with eDNA samples. However, more than half of the member states' methods include at least one metric related to age or size structure and would have to adapt their current fish index if reliant solely on eDNA‐derived information. Most trait‐based metrics expressed in richness are higher when computed from eDNA than when computed from TEF samples. Comparable values are obtained only when the TEF sampling effort increases. Depending on the species trait considered, most trait‐based metrics expressed in relative abundance are significantly higher for eDNA than for TEF samples or vice versa due to over‐estimation of sub‐surface species or under‐estimation of benthic and rare species by TEF sampling, respectively. An existing predictive fish index, adapted to make it compatible with eDNA data, delivers an ecological assessment comparable with the current approved method for 22 of the 25 sites tested. Its associated uncertainty is lower than that of current fish indices. Recommendations for the development of future fish eDNA‐based indices and the associated eDNA water sampling strategy are discussed.